PERBEDAAN JUMLAH KOLONI JAMUR Candida albicans PADA MEDIA Sabouraud Dextrose Agar (SDA) DAN MEDIA MODIFIKASI BIJI NANGKA (Artocarpus heterophyllus lamk) - Anjas Prayoga; Bastian Bastian; Aristoteles Aristoteles (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2023)
Candida albicans is a fungus that lives as normal flora in certain parts of the human body which can instantly become pathogenic if the patient experiences changes or decreases in body resistance. One of the diagnoses for the Candida albicans fungus is culturing, namely isolating it on gowth media such as Sabouraud Dextrose Agar (SDA), but in some areas, it is difficult to use this medium because the price is quite expensive. Jackfruit seeds contain many nutrients needed by fungi such as protein, carbohydrates, and other minerals so that they can gow the Candida albicans fungus, this study aims to determine the difference in the number of Candida albicans colonies on SDA media and jackfruit seed modification media. The research method used a pure experiment. This research was conducted at the microbiology laboratory of the IKesT Muhammadiyah Palembang with a total of 32 samples. The results showed that the average number of colonies of Candida albicans on SDA was 112 CFU/mL media and jackfruit seed modified media 156 CFU/mL. Wilcoxon test obtained a p-value of 0.05 with a value of 0.000. This study concludes that there were differences between SDA media and jackfruit seed modification media.